Analisis Prosedur Penyimpanan Arsip Dinamis Aktif di Balai Pemberdayaan Industri Persepatuan Indonesia - Sri Defa Darmayanti; Evi Suwarni (INDO PUBLISHING, 2026)
This study aims to analyze the active records storage procedures at the Balai Pemberdayaan Industri Persepatuan Indonesia (BPIPI). The study employed a descriptive method with a qualitative approach to obtain an in-depth understanding of records storage practices implemented in the institution. Data were collected through observation, interviews, and documentation involving archivists and employees responsible for records management. The data were analyzed using the Miles and Huberman interactive model, which includes data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that active records storage at BPIPI applies a subject-based filing system. The storage procedure consists of records examination, indexing, classification, and storage. Records are examined to ensure completeness, indexed according to subject matter, grouped based on similar activities or issues, and stored in folders and archival boxes placed in roll o'pack cabinets. The implementation of these procedures has contributed to more systematic records management. However, several obstacles remain, including the absence of records labeling and limited storage facilities. Therefore, improvements in storage facilities and the implementation of records labeling are needed to enhance the effectiveness of active records management.